Analysis of microorganisms and antibiotic resistance in medical instruments in the central sterile supply department (CSSD) of hospitals before and after sterilization - Hapsari Woro; Sajidan; Suranto; Hikmayani Nur Hafidha (BIO Web of Conferences)
Sterilization is essential in preventing the spread of pathogenic bacteria and antibiotic resistance in hospital settings. This study examines the microbial growth and antibiotic resistance of seven medical instruments from the Central Supply Sterile Department, before and after sterilization. The instruments analyzed include arterial clamps, anatomical forceps, tissue scissors, surgical forceps, nal puder, open small tray, and instrument tray. The methodology involved in vitro microbiological testing, including Gram staining, colony counting, and the Vitek 2 system for bacterial identification and antibiotic susceptibility testing (AST). Results showed that before sterilization, nal puder was contaminated with Staphylococcus hominis ssp hominis (Gram-positive) and Bacillus sp. (Gram-positive), while the instrument tray was contaminated with Pseudomonas stutzeri (Gramnegative). After sterilization and a 90-day storage period, Staphylococcus hominis ssp hominis was detected on the open small tray. AST revealed an increase in bacterial sensitivity to antibiotics, from 12 to 14 types poststerilization. The minimum inhibitory concentration (MIC) for Benzylpenicillin decreased from 0.25 μg/mL (resistant) to ≤0.03 μg/mL (sensitive). This study highlights the critical role of sterilization in infection control and antibiotic resistance management in healthcare settings.